Multistage methanolysis of crude palm oil for biodiesel production in a pilot plant - Sani, Winardi (2014)
Crude palm oil (CPO), which is available in abundant in Malaysia, is used as the feedstock in this research work. The work starts with the analysis of the physical and chemical properties of the feedstock and the associated product to obtain the major fatty acid compositions of triglyceride applicable in the crude palm oil. The kinetic models describing the change in the concentrations of the triglycerides, intermediates, alcohol, and the products during the reaction course are formulated through the corresponding kinetic mechanism. By looking at the kinetic mechanisms of the reaction, the chemical reaction is better understood. The ultimately proposed kinetic models of the biodiesel production from crude palm oil and methanol under the presence of a base catalyst follow the second order differential equations without a shunt reaction. The emphasis of this research work is on the study of the methanolysis of the crude palm oil under a base catalyst (transesterification) to produce biodiesel at high quality and maximum yield. The concentration profiles of the reactants and the products employed in the transesterification are obtained by solving numerically the associated differential equations with introducing the published reaction rate constants applied in a laboratory scale. The effect of the reversible transesterification reaction shows that each concentration profile of the reactants and the products tends to achieve an equilibrium after certain reaction time. The simulation results of the kinetic models are implemented in the pilot plant to produce biodiesel from CPO. Due to impurities such as unwanted gums and pigment, the feedstock must first undergo a physical treatment including degumming and bleaching processes. The high content of water and free fatty acid containing in CPO requires an esterification process. The main objective of this process is to lower that value to a minimum level to avoid the undesired effects such as saponification and inefficiency of the catalyst. Methanolysis of triglyceride under an alkaline catalyst, transesterification, can be subsequently carried out. Production of biodiesel in a larger scale needs a particular material handling compared to that in laboratory scale. Uncertainty of isothermal state during the reaction iv course, uniform mixing in the catalyst preparation, and the effect of the inert gas as the process safety agent will affect adversely the conversion and also the yield. Consequently, the transesterification process must be carried out in stages to achieve a high conversion of palm oil to biodiesel. To attain this objective, the molar ratio of palm oil to methanol for each stage can be adjusted to minimize the methanol usage and the steam consumption. In a batch–mode operated plant, the conversion can vary from a batch to a another batch process. With this approach, it is expected that the high conversion above 96.5 % by weight, as requested by EN 14214 standard, as well as a high yield of biodiesel can be achieved. Gas chromatography (GC) analysis method was used to determine the methyl ester contents during the reaction progress. Based on these accurate experiment data along with the simulation results, a validation was done. Technical improvements in the plant operation can therefore be deduced towards the best plant performance and a high quality of biodiesel product.